2013
DOI: 10.1155/2013/421821
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT3 in Cancer Metastasis and Translational Advances

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a latent cytoplasmic transcription factor, originally discovered as a transducer of signal from cell surface receptors to the nucleus. It is activated by tyrosine phosphorylation at position 705 leading to its dimerization, nuclear translocation, DNA binding, and activation of gene transcription. Under normal physiological conditions, STAT3 activation is tightly regulated. However, compelling evidence suggests that STAT3 is constitutively activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
272
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(277 citation statements)
references
References 139 publications
(158 reference statements)
3
272
0
2
Order By: Relevance
“…In this study, we found that ATF3 was upregulated in skin cancer tissues from patients and that ATF3 promoted skin cancer cell proliferation through activating Stat3 phosphorylation, which is the hallmark of various cancers development (Hodge et al, 2005;Yu et al, 2009;Kamran et al, 2013). Furthermore, activation of Stat3 by ATF3 was dependent on repression of p53 expression and the induction of p53-Stat3 signaling cascade accounted for the promotion effect of ATF3 on skin cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 68%
“…In this study, we found that ATF3 was upregulated in skin cancer tissues from patients and that ATF3 promoted skin cancer cell proliferation through activating Stat3 phosphorylation, which is the hallmark of various cancers development (Hodge et al, 2005;Yu et al, 2009;Kamran et al, 2013). Furthermore, activation of Stat3 by ATF3 was dependent on repression of p53 expression and the induction of p53-Stat3 signaling cascade accounted for the promotion effect of ATF3 on skin cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 68%
“…The three main mechanisms by which SOCS protein can inhibit STAT3 signaling involves, i) by competing with STAT3 for binding to pTyr motif of activated receptor, ii) by directly binding to JAK receptor and inactivating it, or iii) by binding to signaling protein and targeting it for proteasomal degradation through SOCS box domain [40]. Apart from acting as inhibitor of STAT3 signaling, SOCS3 is also a downstream transcriptional target of STAT3 pathway.…”
Section: Socs3 Proteinsmentioning
confidence: 99%
“…However, under normal condition the SOCS3 signaling is under stringent control. In several cancers, the loss of SOCS3 expression due to epigenetic alteration leads to enhanced STAT3 signaling that in turn increases overall cell survival and proliferation [40,41]. In breast cancer patients, loss of SOCS3 expression was considered as a biomarker for poor prognosis and was shown to be associated with increased lymph node metastasis [42].…”
Section: Socs3 Proteinsmentioning
confidence: 99%
“…Stat3 was revealed as the nodal convergence point between PR and HRG/ErbB-2 signaling in BC (Proietti et al 2005(Proietti et al , 2009). Interestingly, Stat3 plays a key role in mammary cancer (reviewed in Kamran et al 2013). Nuclear interaction between PR and ErbB-2 was next identified, showing that PR activated by its ligands (the steroid hormones progestins) induces ErbB-2 nuclear translocation and its colocalization and physical association with Stat3 in the nuclear compartment of BC cells.…”
Section: :12mentioning
confidence: 99%
“…The critical role of both Stat3 and MErbB-2 in BC metastasis has long been demonstrated (reviewed in Freudenberg et al 2009, Kamran et al 2013. Furthermore, a series of BC models where transgenic mice carry ErbB-2 under the control of the mouse mammary tumor virus (MMTV) promoter disclosed the involvement of Stat3 as a downstream effector of MErbB-2-induced metastatic dissemination in BC (Muller et al 1988, Guy et al 1992, Siegel et al 1999, Finkle et al 2004, Ursini-Siegel et al 2008.…”
Section: :12mentioning
confidence: 99%